2011
DOI: 10.2215/cjn.06770711
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Associations of Reduced Estimated Glomerular Filtration Rate with Concurrent Chronic Kidney Disease Complications

Abstract: SummaryBackground and objectives It has been suggested that moderate reductions in estimated GFR (eGFR) among older adults may not reflect chronic kidney disease (CKD).Design, setting, participants, & measurements We examined age-specific (Ͻ60, 60 to 69, 70 to 79, and Ն80 years) associations between eGFR level and six concurrent CKD complications among 30,528 participants from the National Health and Nutrition Examination Survey (NHANES) 1988(NHANES) to 1994(NHANES) and 1999(NHANES) to 2006 (n ϭ 8242 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
64
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 38 publications
8
64
1
2
Order By: Relevance
“…However, anemia caused by nutritional insufficiency is more common in stages 1 and 2 CKD (18). A positive correlation between the degree of anemia and the degree of kidney insufficiency has been previously reported (19,20). The results of the present study indicated that the level of Hb decreased with decreasing renal function.…”
Section: Discussionsupporting
confidence: 75%
“…However, anemia caused by nutritional insufficiency is more common in stages 1 and 2 CKD (18). A positive correlation between the degree of anemia and the degree of kidney insufficiency has been previously reported (19,20). The results of the present study indicated that the level of Hb decreased with decreasing renal function.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, the CKD-EPI is not more accurate than the MDRD in elderly patients. In addition, as pointed out by Bowling et al, their study lacked demographic diversity, suggesting that more investigation of ethnically diverse elderly patients with CKD is needed (8).…”
mentioning
confidence: 97%
“…Their evaluation of anemia, acidosis, hyperphosphatemia, hypoalbuminemia, and hypertension in more than 30,000 participants in the NHANES data and hyperparathyroidism in more than 8000 participants suggests that reductions in eGFR in elderly patients are not simply age-related declines equating to normal kidney function. Perhaps more importantly, they found that moderate reductions in eGFR (45 to 59 ml/min per 1.73 m 2 ) are associated with anemia, acidosis, hyperparathryoidism, and, more marginally, hyperphosphatemia in those over 80 years of age compared with similarly aged people with eGFR Ͼ60 ml/min per 1.73 m 2 (8). Importantly, elderly patients with eGFR Ͻ45 ml/min per 1.73 m 2 had nearly twice the prevalence ratios of these complications.…”
mentioning
confidence: 97%
See 2 more Smart Citations